Perception of Charisma, Comfort, Micro and Macro Expressions in Computer Graphics Characters - Andreotti, Lucas; Weber, Morgana Luiza; Silva, Tiago Luz da; Araujo, Victor Flávio De Andrade; Musse, Soraia Raupp (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
This paper presents the reproduction of a research focused on the perception of micro and macro expressions of a character generated by Computer Graphics (CG), firstly described in 2014. Our main goal is to investigate whether the perceptual analysis of CG characters in 2014 is similar to people's perception in 2021. We also performed other analyses, such as the impact of familiarity with CG technologies, gender, age and education on the perception of micro and macro expressions, by subjects. In addition to the perceptual analysis of micro and macro expressions, we also evaluate the perceived comfort and charisma in relation to the presented CG characters.